(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Evaluate the effectiveness of electroacupuncture combined with urinary training in the treatment of postpartum urinary retention compared to urine training alone, thereby determining whether electroacupuncture can become a viable alternative method, effective in treating postpartum urinary retention. Subjects and methods: Clinical trial, prospective study, using acupoints quan nguyen, qi hai, trung pole, khuc cot and tam yin giao on both sides to perform electroacupuncture with frequency of 60 Hz, intensity 2-10 mA for 20 minutes. Main variables include: residual urine volume, continence recovery rate, and continence recovery effectiveness. Keywords: Electroacupuncture, postpartum urinary retention, bladder ultrasound, bladder training. Results: After 2-3 hours of treatment, the percentage of residual urine volume in the electroacupuncture group decreased by 53.21%, more than the control group (reduced by 32.52%), but the difference was not significant statistical significance (p > 0.05); the electroacupuncture group had higher urination recovery results (85.53%) than the control group (59.21%) with p < 0.05; the electroacupuncture group had good and fair recovery results (84.21%) than the control group (77.64%) with p < 0.05. Conclusions: The recovery rate after electroacupuncture combined with urinary exercises to treat postpartum urinary retention in pregnant women reached 85.53%. Electroacupuncture is a safe and effective method of treating postpartum urinary retention and can be used instead of traditional methods such as catheterization.